Molecular epidemiology of vancomycin-resistant Enterococcus faecium in Argentina - Corso, Alejandra (2007)
Fil: Corso, Alejandra. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Servicio Antimicrobianos; Argentina.